Extension of the crRNA enhances Cpf1 gene editing in vitro and in vivo - Hyo Min Park (Nature Portfolio, 2018)
Optimization of the recently discovered Class 2 CRISPR protein Cpf1 has the potential to promote its applications in gene editing and therapeutics. Here, the authors find that extending the 5′ end of the crRNA can increase both the editing efficiency and delivery of Cpf1 in vitro and in vivo.